Indonesian Translation and Adaptation of Social Appearance Anxiety Scale (SAAS) for Early Adolescent Girls in Indonesia - Putri BBK; Noer AH; Pebriani LV; Purba FD (Psychology Research and Behavior Management)
Bernadette Btari Kania Putri, Afra Hafny Noer, Lucia Voni Pebriani, Fredrick Dermawan Purba Department of Psychology, Faculty of Psychology, Universitas Padjadjaran, Jatinangor, West Java, IndonesiaCorrespondence: Bernadette Btari Kania Putri, Department of Psychology, Faculty of Psychology, Universitas Padjadjaran, Ir. Soekarno Street KM.21, Hegarmanah, Jatinangor, Kabupaten Sumedang, West Java, 45363, Indonesia, Email bernadette20002@mail.unpad.ac.idBackground: During adolescence, the attention of individuals has been observed to increasingly shift toward respective appearances, and this is primarily influenced by the various stages of puberty. Previous studies have reported that early body image disturbances may have long-term mental health impacts that persist into adulthood.Purpose: This study aimed to translate and validate Social Appearance Anxiety Scale (SAAS), developed by Hart et al, for use among early adolescent girls in Indonesia.Patients and Methods: In order to achieve the stated objective, an adaptation process, guided by the International Test Commission (ITC) Guidelines for Adapting Tests was carried out. The process consisted of three stages including 1) forward and backward translations, 2) testing of reliability coefficients, and 3) collecting validity evidence through content-based and construct-based testing using Confirmatory Factor Analysis (CFA). Data were collected online from respondents in Bandung, Indonesia, who were then asked to participate in a retest 1 month later. The final sample comprised 197 girls aged 10– 14 years.Results: The obtained results showed that content validity achieved an agreement rate exceeding 90%, and SAAS was observed to possess excellent internal consistency (Cronbach’s α = 0.932). Accordingly, test-retest reliability was stable (ICC (95% CI) = 0.850), convergent validity between SAAS and Social Anxiety Scale for Adolescents (SAS-A) was significantly positive (r = 0.439; p < 0.001), and CFA signified an acceptable model fit after modification (Model Chi-Square, p > 0.05; RMSEA = 0.036 < 0.08; CFI = 1 ≥ 0.90; GFI = 0.94 ≥ 0.90; Loading Factors > 0.3).Conclusion: SAAS-Indonesia was observed to be sufficiently reliable and valid for use among early adolescent girls in Indonesia.Keywords: social appearance anxiety, psychometric property, adolescents